An Innovative Approach for Risk Identification and Management in Software Projects - Joshy, Angel P; Natarajan, K; Pani, Alok Kumar (International Journal of Computer Sciences and Engineering, 2019)
Risk is a potential issue that may trade off the achievement of a product advancement venture. The success of a project is altogether impacted by the risk management. The exactness of risk assessment specifically impacts the adequacy of risk management. In this paper, we examine the chance components. The Risk-matrix has been inspected and a checklist is made to perceive the significance of the risk .This paper deals with the risk factors identified with risk estimation ,risk analysis, venture board, risk scope, prerequisites and hazard factors identified with client fulfilment .Here we are adopting a method which consists of 2 phases. The first one is the risk identification and second is the risk management planning. Identification of the risk involves analytical methods like a risk checklist which evaluates the risk and risk assessment matrix. In risk checklist the probability of occurrences is taken and the possible negative effects for each risk is identified. Management of the risk involves various measures to be adopted to reduce the probability of risk events and to reduce the negative impacts of the risk events.